CPAP promotes timely cilium disassembly to maintain neural progenitor pool. (29th February 2016) - Gabriel, Elke; Wason, Arpit; Ramani, Anand; Gooi, Li Ming; Keller, Patrick; Pozniakovsky, Andrei; Poser, Ina; Noack, Florian; Telugu, Narasimha Swamy; Calegari, Federico; Šarić, Tomo; Hescheler, Jürgen; et al.
Abstract: A mutation in the centrosomal‐P4.1‐associated protein (CPAP) causes Seckel syndrome with microcephaly, which is suggested to arise from a decline in neural progenitor cells (NPCs) during development. However, mechanisms of NPCs maintenance remain unclear. Here, we report an unexpected role for the cilium in NPCs maintenance and identify CPAP as a negative regulator of ciliary length independent of its role in centrosome biogenesis. At the onset of cilium disassembly, CPAP provides a scaffold for the cilium disassembly complex (CDC), which includes Nde1, Aurora A, and OFD1, recruited to the ciliary base for timely cilium disassembly. In contrast, mutated CPAP fails to localize at the ciliary base associated with inefficient CDC recruitment, long cilia, retarded cilium disassembly, and delayed cell cycle re‐entry leading to premature differentiation of patient iPS‐derived NPCs. Aberrant CDC function also promotes premature differentiation of NPCs in Seckel iPS‐derived organoids. Thus, our results suggest a role for cilia in microcephaly and its involvement during neurogenesis and brain size control. Synopsis: Mutations in centrosomal‐P4.1‐associated protein (CPAP) cause Seckel syndrome. CPAP defects prevent proper cilium disassembly in neural progenitor cells with cell cycle progression delay and premature differentiation, leading to the microcephaly associated with this syndrome. In wild‐type NPCs, CPAP‐mediated CDC recruitment allows timely cilium disassembly and normal G1‐S transition. This enables WT NPCs to undergo symmetric proliferation and NPC pool expansion. In failure of efficient CPAP‐mediated CDC recruitment, Seckel NPCs exhibit a retarded cilium disassembly and an extended G1‐S transition (extended red arrow). This triggers premature NPC differentiation leading to NPC loss and microcephaly. Abstract : Mutations in centrosomal‐P4.1‐associated protein (CPAP) cause Seckel syndrome. CPAP defects prevent proper cilium disassembly in neural progenitor cells with cell cycle progression delay and premature differentiation, leading to the microcephaly associated with this syndrome.